Al-Uqud Al-Murakkabah: Memahami Konsep dan Penerapannya dalam Hukum Islam di Indonesia - Mimin Mintarsih; Abdillah abdillah; Saehudin Saehudin (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2025)
This article discusses the concept of al-uqud al-murakkabah or complex contracts in Islamic law, focusing on its application in Indonesia. Al-uqud al-murakkabah refers to an agreement that combines various legal elements in one contract, different from a simple contract that involves only one type of transaction. Using a qualitative and descriptive-analytical approach, this research examines the theory and practice of al-uqud al-murakkabah in Islamic Law in Indonesia. Through a literature study, this article presents an in-depth understanding of the concept of complex contracts, its types such as ijarah muntahiya bittamlik, murabaha, tawarruq, musharakah, and mudharabah, and how they are applied in Islamic financial institutions in Indonesia. The research findings show that the application of al-uqud al-murakkabah in Indonesia faces challenges in terms of compliance with sharia principles and regulations, but also offers significant opportunities for the development of more flexible Islamic financial products. This article provides recommendations to improve the effectiveness of the application of complex contracts in the context of Islamic law and the Islamic financial system in Indonesia.